Respostas

2013-08-01T14:08:29-03:00
D)102=65+t
102-65=t
t=37

e)z+9=9+10
z=19-9
z=10


f)96=98+p
96-98=p
p=-2


g)23-z=22
-z=22-23
-z=-1  *(-1)
z=1


h)89=x-11
89+11=x
x=100

i)y-199=1999
y=1999+199
y=2198


j)1024=1025-k
1024-1025=-k
-k=-1
k=1
2013-08-01T14:15:11-03:00
D)   102=65+t
       t=65-102
        t=37
E)z+9=9+10
   z=19-9
    z+10
F)96=98+p
  p+98-96
   p=2
G)23-z=22
  -z=22-23
    -z=-1   * (-1)
     z=1
H) 89=x+11
     x= -11-89
     x=100
I)  y-799=1999
     y=1999+199
     y=2198
J) 1024=1025-k
    k=1025-1024
     k=1